Reporters transiently transfected into mammalian cells are highly sensitive to translational repression induced by dsRNA expression. - Jana Nejepinska (Public Library of Science (PLoS), 2014)
In mammals, double-stranded RNA (dsRNA) can mediate sequence-specific RNA interference, activate sequence-independent interferon response, or undergo RNA editing by adenosine deaminases. We showed that long hairpin dsRNA expression had negligible effects on mammalian somatic cells--expressed dsRNA was slightly edited, poorly processed into siRNAs, and it did not activate the interferon response. At the same time, we noticed reduced reporter expression in transient co-transfections, which was presumably induced by expressed dsRNA. Since transient co-transfections are frequently used for studying gene function, we systematically explored the role of expressed dsRNA in this silencing phenomenon. We demonstrate that dsRNA expressed from transiently transfected plasmids strongly inhibits the expression of co-transfected reporter plasmids but not the expression of endogenous genes or reporters stably integrated in the genome. The inhibition is concentration-dependent, it is found in different cell types, and it is independent of transfection method and dsRNA sequence. The inhibition occurs at the level of translation and involves protein kinase R, which binds the expressed dsRNA. Thus, dsRNA expression represents a hidden danger in transient transfection experiments and must be taken into account during interpretation of experimental results.